2014
DOI: 10.2147/ijn.s57938
|View full text |Cite
|
Sign up to set email alerts
|

Optical imaging of absorption and distribution of RITC-SiO2 nanoparticles after oral administration

Abstract: Purpose In this study, we investigated the absorption and distribution of rhodamine B isothiocyanate (RITC)-incorporated silica oxide nanoparticles(SiNPs) (RITC-SiNPs) after oral exposure, by conducting optical imaging, with a focus on tracking the movement of RITC-SiNPs of different particle size and surface charge. Methods RITC-SiNPs (20 or 100 nm; positively or negatively charged) were used to avoid the dissociation of a fluorescent dye from nanoparticles via spontan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The detection was based on a fluorescent marker; the authors did not acknowledge potential nanoparticle degradation issues. In [ 35 ], silica nanoparticles were not found in the brain of rats within 90 days after oral and dermal administration; a similar study conducted on mice, did not find silica nanoparticles the brain within 10 hours after oral exposure [ 36 ]. In [ 37 ], magnetic nanoparticles overcoated with silica were detected in the brain after intraperitoneal administration.…”
Section: Resultsmentioning
confidence: 99%
“…The detection was based on a fluorescent marker; the authors did not acknowledge potential nanoparticle degradation issues. In [ 35 ], silica nanoparticles were not found in the brain of rats within 90 days after oral and dermal administration; a similar study conducted on mice, did not find silica nanoparticles the brain within 10 hours after oral exposure [ 36 ]. In [ 37 ], magnetic nanoparticles overcoated with silica were detected in the brain after intraperitoneal administration.…”
Section: Resultsmentioning
confidence: 99%
“…These characteristics are already being exploited for breast cancer detection [9,16,23], melanoma imaging [12,18] and tumor visualization in small animals [24,46]. In addition, the potential of silica-coated super paramagnetic iron oxide nanoparticles has been demonstrated in ex vivo muscular tissue [4] and multiple studies have shown the potential of various nanoparticle dispersions for photoacoustic enhancement [17,25,26].…”
Section: Introductionmentioning
confidence: 99%